Diversity and species richness of land snails inhabiting an impacted macro-zone-Mfamosing limestone hill in Sub-Saharan Region - Ehimen Godswill Eguakhide; Victory Onyekachukwu Osiele; Osikemekha Anthony Anani (Global Ecology and Conservation, 2023)
The land snail diversity and abundance and some ecological aspects of the fauna in a threatened limestone hill in Mfamosing, Cross Rivers state, Nigeria was investigated between May 2017 and June 2018. Twelve plots of 10 m x 10 m each using a combination of leaf litter in the forest floor (litter and topsoil in a total of ninety sample bags) were sampled from which shells were extracted by handpicking. A total of 289 (two hundred and eighty-nine) specimens representing twenty-three species in seven molluscan families were recorded. The carnivorous Streptaxidae family dominated the fauna regarding species richness while the family Urocyclidae dominated species abundance. The families Eucolinidae and Aillyidae accounted for the least dominant species. The family Streptaxidae with seven species accounted for over 30% of the mollusk abundance, while Urocyclidae had the highest number of individual specimens. True estimates of diversity using Chao2 and second-order Jack-Knife estimators yielded 25 and 24 species respectively. The Land Snail diversity in Mfamosing limestone hill when compared with those from other parts of Nigeria (Okomu in Edo State) and some other parts of the world (Sabah, Malaysia) is relatively high, with moderate levels of species abundance, showing relatively high differentiation, local dominance and endemism by few species. This reveals that Mfamosing limestone hill is one of the biodiversity hotspots for terrestrial mollusks and requires urgent conservation measures, given the current rate of Limestone quarrying in the region.